2018
DOI: 10.1111/pedi.12769
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life of adolescents with type 1 diabetes in the context of resilience

Abstract: Significant association can be observed between HRQoL and RS. Supposedly, higher level of PA promotes higher level of RS that in turn helps increase HRQoL in adolescents with T1D. Treatment with insulin pump therapy also promotes better HRQoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
23

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 38 publications
0
19
0
23
Order By: Relevance
“…Chewing and spitting out food as a compensatory behavior should be taken into account particularly if associated with weight gain and increased insulin requirement. Deterioration of metabolic control might also impair quality of life and resilience levels [63].…”
Section: Patient Education and Psychological Carementioning
confidence: 99%
“…Chewing and spitting out food as a compensatory behavior should be taken into account particularly if associated with weight gain and increased insulin requirement. Deterioration of metabolic control might also impair quality of life and resilience levels [63].…”
Section: Patient Education and Psychological Carementioning
confidence: 99%
“…Los artículos incluidos en el estudio para su análisis son 25 (tablas 1 y 2) y la mayoría fueron obtenidos desde la base de datos bibliográfica MEDLINE. El inglés fue el idioma predominante [13][14][15][16][17][18][19][20][21][22][24][25][26][27][28][29][30][31][32][33][34][35] y en el año 2018 fueron publicados la mayor parte de ellos, 7 (28%) [30][31][32][33][34][35][36] . La revista académica más utilizada para la publicación de los artículos fue la Pediatric Diabetes 15,26,31,33 .…”
Section: Resultsunclassified
“…El inglés fue el idioma predominante [13][14][15][16][17][18][19][20][21][22][24][25][26][27][28][29][30][31][32][33][34][35] y en el año 2018 fueron publicados la mayor parte de ellos, 7 (28%) [30][31][32][33][34][35][36] . La revista académica más utilizada para la publicación de los artículos fue la Pediatric Diabetes 15,26,31,33 . Se encontraron investigaciones desarrolladas en 4 continentes: en Europa, 9 publicaciones 14,15,17,19,22,25,[29][30][31] ; en Asia, 4 publicaciones 13,18,20,24 ; en África, 1 publicación 28 y en América, 11 publicaciones 16,19,21,…”
Section: Resultsunclassified
See 1 more Smart Citation
“…International diabetes guidelines therefore increasingly recommend the use of HRQOL measurement instruments to guide routine care [13]. The vast majority of HRQOL studies so far have been performed in children or adolescents with T1DM [1,[14][15][16], while reports regarding HRQOL in young adults are scarce [9,[17][18][19]. In a study in a large global cohort of youth with T1DM (8-25 years), the 19-25 age group reported poorer HRQOL than did the younger age groups [17].…”
Section: Introductionmentioning
confidence: 99%